2019
DOI: 10.20945/2359-3997000000142
|View full text |Cite
|
Sign up to set email alerts
|

Heterotaxy syndrome with agenesis of dorsal pancreas and diabetes mellitus: case report and review of the literature

Abstract: Heterotaxy syndrome (HS) is a rare congenital condition with multifactorial heritance, characterized by an abnormal arrangement of thoraco-abdominal organs and vessels. Patients present with multiple cardiac, gastrointestinal, hepatosplenic, pancreatic, renal, neurological and skeletal disorders without any pathognomonic alteration. Despite the described increased risk of diabetes mellitus (DM) in patients with altered pancreatic anatomy, just one case was reported in Korea regarding the association of HS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…At diagnosis, she presented with a clamp‐determined FBM that was 50% higher than the average in normoglycemic controls. This finding is at variance with previous cases of HS and DPA that were associated with diabetes 13,14 . Also, in isolated DPA, more than half of patients have diabetes at the time of diagnosis 5,6 .…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…At diagnosis, she presented with a clamp‐determined FBM that was 50% higher than the average in normoglycemic controls. This finding is at variance with previous cases of HS and DPA that were associated with diabetes 13,14 . Also, in isolated DPA, more than half of patients have diabetes at the time of diagnosis 5,6 .…”
Section: Discussioncontrasting
confidence: 78%
“…This finding is at variance with previous cases of HS and DPA that were associated with diabetes. 13,14 Also, in isolated DPA, more than half of patients have diabetes at the time of diagnosis. 5,6 For these reasons, deceased donors with DPA are in general not considered suitable for whole organ pancreas transplantation and are also discouraged from islet isolation; one report, however, did mention a successful islet cell allotransplantation following isolation from a deceased donor with partial DPA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, parental counselling would include the likelihood of congenital diabetes mellitus and malabsorption in a case involving pancreatic agenesis, or the likelihood of recurrent pancreatitis and increased risk for neoplasia of the residual pancreas in a case involving dorsal agenesis of the pancreas. [17][18][19][20] Several studies have reported the association between the TCF2 (HNF1B) gene and fetal renal malformations and agenesis or hypoplasia of the pancreas. [21][22][23] In these cases, however, the pancreatic malformation was not diagnosed prenatally but following postmortem examinations of the abortus.…”
Section: Discussionmentioning
confidence: 99%